Role of genetic aspect in pathogenesis of atopic dermatitis - Wesserlking, Martyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2013)
The pathogenesis of atopic dermatitis (AD) is a very complicated process that involves an intricate array of molecules. Nowadays it is generally accepted that cytokines play an important role in the progression of the clinical presentation of atopic dermatitis. However, emerging data point to the possible involvement of cornified envelope proteins in the development of skin barrier dysfunction and illness. Unfortunately, our knowledge on relation of particular genotype to progression of AD is very limited. Therefore, intensive studies are needed to increase our understanding of genetic background of atopic dermatitis. Hopefully the future research will identify new factors that help us to determine the additional risk for certain patients with atopic dermatitis.